2017
DOI: 10.1139/apnm-2016-0443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training and estrogen replacement on adipose tissue inflammation in ovariectomized rats

Abstract: Estrogen deficiency is directly related to central obesity and low-grade inflammation. Hormonal replacement and exercise training are both able to decrease fat accumulation and inflammation in postmenopausal women. However, the efficiency of resistance training (RT) and estrogen replacement (ER) in minimizing adiposity and inflammation in the visceral adipose tissue (VAT) of ovariectomized (OVX) rats has not yet been elucidated. In this study, Sprague-Dawley rats were divided into the following 6 groups: sham-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…; Rodrigues et al . ). However, HR is related to the increased incidence of some types of cancer (Zhang et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Rodrigues et al . ). However, HR is related to the increased incidence of some types of cancer (Zhang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Currently, there is great interest in investigating strategies to prevent or attenuate the effects of accumulating adipose tissue and low-intensity chronic inflammation associated with obesity in the postmenopausal period (Arslan et al 2010;Gregor & Hotamisligil 2011). Hormone replacement (HR) has shown beneficial effects in terms of preventing oxidative stress and adipocyte inflammation (Stubbins et al 2012;Rodrigues et al 2017). However, HR is related to the increased incidence of some types of cancer (Zhang et al 2007), which limits its use.…”
Section: Introductionmentioning
confidence: 99%
“…According to all these algorithms, our results show that the three most stable genes were Hprt1, Tbp, and Rpl32 for IBAT and Tbp, B2m, and Hprt1 for RWAT, while the least stable genes were 18S, Actb, and Gapdh for both tissues. The Actb and Gapdh genes are widely used in the literature as normalizers for the evaluation of target gene expression in WAT and BAT (Aguirre et al, 2016;Antony et al, 2017;Calderon-Dominguez et al, 2016;Chang and Kim, 2017;Li et al, 2015;Rodrigues et al, 2017;Tsubai et al, 2016;Yan et al, 2017), however, a few authors argue about the stability of the reference genes. A systematic review showed that the vast majority of the studies use a single gene as a normalizer, with Actb and/or Gapdh being commonly selected to evaluate the gene expression in vertebrates (Chapman and Waldenstrom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, estrogen deprivation promotes immune cell infiltration and increased tissue inflammation because estrogen influences immune and inflammatory conditions [ 41 ]. Indeed, adipose tissue inflammation is elevated in OVX animals and postmenopausal women [ 42 44 ]. It is believed that the increase in proinflammatory cytokines contributes to the development of various chronic diseases, including osteoporosis, atherosclerosis, liver disease, and cancer [ 27 , 45 ].…”
Section: Discussionmentioning
confidence: 99%